2011
DOI: 10.1007/s11295-011-0417-z
|View full text |Cite
|
Sign up to set email alerts
|

Examination of expansin genes as related to apple fruit crispness

Abstract: The possible relationship of seven expansin genes to maintenance of apple (Malus × domestica Borkh.) crispness during storage was examined. Expression of expansin genes MdEXPA1, MdEXPA2, MdEXPA3, MdEXPA4, MdEXPA5, and MdEXPA7 was quantified among apple cultivars that remained crisp or lost crispness between harvest and after 8 weeks of cold storage. MdEXPA1 was expressed in low quantities in fresh fruit while expression of MdEXPA4, MdEXPA5, and MdEXPA7 was not detected among fresh or cold-stored apple cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…MdACS1-1 is associated with high ethylene production and softer fruit, while MdACS1-2 is associated with low ethylene production and firmer fruit [ 12 ]. The high expression of MdACS1 in ’Honeycrisp’ fruit corresponds to its heterozygous allelotype, including both MdACS1-1 and MdACS1-2 , in contrast to that of the homozygous ( MdACS1-2/2 ) MN1764 [ 26 ], but is inconsistent with its ripening behavior, including crispness retention. Despite exhibiting high MdACS1 expression, ’Honeycrisp’ fruit produce low amounts of ethylene during ripening compared with ’McIntosh’ fruit, that show climacteric ripening characteristics [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MdACS1-1 is associated with high ethylene production and softer fruit, while MdACS1-2 is associated with low ethylene production and firmer fruit [ 12 ]. The high expression of MdACS1 in ’Honeycrisp’ fruit corresponds to its heterozygous allelotype, including both MdACS1-1 and MdACS1-2 , in contrast to that of the homozygous ( MdACS1-2/2 ) MN1764 [ 26 ], but is inconsistent with its ripening behavior, including crispness retention. Despite exhibiting high MdACS1 expression, ’Honeycrisp’ fruit produce low amounts of ethylene during ripening compared with ’McIntosh’ fruit, that show climacteric ripening characteristics [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a genetic study, Harb et al [ 8 ] showed that MdEXP2 and MdXTH2 had lower gene expression in ’Honeycrisp’ fruit during fruit ripening compared with ’McIntosh’ fruit, while MdXTH10 exhibited an opposite expression pattern. Trujillo et al [ 26 ], on the other hand, found that MdEXP2 was not strongly related to crispness retention by examining the gene expression and effects of allelotype in fruit of several apple varieties and ’Honeycrisp’ progeny individuals. So far, there has been no additional study to validate the functions of MdXTH s in ’Honeycrisp’ fruit, and thus the MdXTH gene family is a potential target for further analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications in the chemical composition of apple cell wall polysaccharides during fruit development and ripening have already been described [ 6 , 9 , 10 , 22 , 30 ] as well as enzymes and genes expression involved in ripening [ 14 , 16 , 17 , 23 , 26 , 27 , 39 , 40 ]. However a more detailed view of genes potentially involved in cell wall polysaccharide chemical composition, structure, water flux during apple development and storage provides insights into the mechanisms affecting texture characteristics and highlights novel candidate genes involved in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…‘Honeycrisp’ has become a popular apple ( Malus × domestica ) cultivar in U.S. markets [1] and an important parent in apple breeding programs worldwide. Its high acclaim has been largely due to its strong consumer preference [2], the uniquely ultra-crisp texture of its fruit [3] that is retained through extended cold storage [4], [5], [6] and its reported resistance to apple scab [7]. However, growers have been concerned about the tendency of ‘Honeycrisp’ trees to develop the leaf disorder termed zonal leaf chlorosis (ZLC) [5].…”
Section: Introductionmentioning
confidence: 99%